Bridging the State and Society: Rethinking of Social Response and Disaster Risk Reduction during Uncertainties Future of Covid-19 in Indonesia - Octastefani, Theresia (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2020)
This study aimed to examine the social aspects of a disaster, in particular related to disaster risk reduction and social response, and to seek the references in adopting or adapting the best practices from a number of countries that have been able to control the Covid-19 spread. To get a comprehensive result, this study used a qualitative method with the data collected through desk studies sourced from the digitally accessed secondary data in the span of January to May 2020. The results of the study showed that unity of command in preparing a strategy of disaster risk reduction from the central government to local governments has become an absolute necessity to achieve a more coordinated and sustainable management effort. This pandemic at the same time becomes an alarming alert and wakeup call for the government to place subscriptions for disease outbreak as a priority agenda. In addition, strengthening the people-centered approach as the spearhead of disaster management must also be done to create a resilient and disciplined social behaviour and responsibility of the community. In the end, the government policy in improving the pandemic situation must be able to bridge public awareness to conform the health protocol as a joint commitment to prevent the new normal scheme not turning into a new disaster in future.